Poor approach to sustainable development: lack of environmental management and scarce emphasis in behaviour change in textbooks of 13 countries - Tracana, Rosa Branca (2008)
Nowadays natural resources are being used in an over exploration way, which implies vast environmental problems such as decrease of biodiversity, green-house effect, pollution. Therefore today it is important to look at the management of the natural resources in order to avoid such great over exploration. School environmental education plays an important role in the learning and awareness of children and young people for environmental issues. In this work we analysed the topic “Use of Resources” in the textbooks from thirteen countries from Europe (West to East: Portugal, France, Italy, Malta, Germany, Hungary, Romania, Lithuania, Estonia, Finland), from Africa (Senegal, Morocco) and from the Middle East (Lebanon), since the first grade till the end of the secondary school. We used a grid constructed in the context of a European Project “Biohead Citizen” (“Biology Health and Environmental education for better citizenship” STREP, CIT2-CT2004-506015, Carvalho et al. 2004). The results showed that the analysed textbooks give little importance to environmental sustainability as there is a general absence about the role of the society intervention in the management as well as of political sustainability. Although behaviour change towards the environment is scarce, there is some more emphasis given to individual change rather than to social change. This textbook weakness may impair young citizens getting aware of the needs for a sustainable development.